Digital Marketing Analysis of Mie Gacoan Customer at Jakarta Using RFM and K-Means Clustering Methode - Alghifari Suhardi, Fitra; Saputro, Andi; Sri Nugroho, Amanda; Heikal, Jerry (Journal of Economics and Business UBS, 2024)
PT. Pesta Pora Abadi or Mie Gacoan is an Indonesian company within the Food and Beverages industry that produces food using noodles. Mie Gacoan is currently thriving with hype and sales, and with those momentum supporting them, they want to take advantage of this moment to expand their business by analysing their customer to market more their products, but they still don’t know Segmentasi is a process of knowing customer characteristics to get profitable customers for the company. Segmentasi will be done by grouping the customers into x categories. This study aims to combine K-means clustering and RFM to analyze the customer segmentation of Mie Gacoan. This customer characteristics will help Mie Gacoan in decision making to prioritize their energy and resources to potential customers or profitable customers.